Body Fat Percentage and the Long-term Risk of Fractures. The EPIC-Norfolk Prospective Population Cohort Study - Pana, Tiberiu A.; Kioh, Sheng Hui; Neal, Samuel R.; Tan, Maw Pin *; Sumaiyah, Mat; Moayyeri, Alireza; Luben, Robert N.; Wareham, Nicholas J.; Khaw, Kay Tee; Myint, Phyo K (Elsevier, 2023)
Background This cohort study aimed to determine the association between body fat percentage (BF%), incident fractures and calcaneal broadband ultrasound attenuation (BUA).